2015
DOI: 10.1177/0265659015620254
|View full text |Cite
|
Sign up to set email alerts
|

Shared knowledge and mutual respect: Enhancing culturally competent practice through collaboration with families and communities

Abstract: Collaboration with families and communities has been identified as one of six overarching principles to speech and language therapists' (SLTs') engagement in culturally competent practice . The aim of this study was to describe SLTs' collaboration with families and communities when engaging in practice to support the speech, language and communication of children from culturally and linguistically diverse backgrounds. The study also aimed to identify the benefits and tensions related to such collaborations and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 35 publications
2
16
0
Order By: Relevance
“…Multilingualism enhances social cohesion by strengthening cultural identity, which facilitates resilience, self-esteem and belonging (Bracey, Bámaca & Umaña-Taylor, 2004). The participants indicated that familial and community networks were important for supporting multilingualism and home language maintenance, corroborating previous research (Verdon, Wong & McLeod, 2016). The availability of resources (e.g.…”
Section: Discussionsupporting
confidence: 81%
“…Multilingualism enhances social cohesion by strengthening cultural identity, which facilitates resilience, self-esteem and belonging (Bracey, Bámaca & Umaña-Taylor, 2004). The participants indicated that familial and community networks were important for supporting multilingualism and home language maintenance, corroborating previous research (Verdon, Wong & McLeod, 2016). The availability of resources (e.g.…”
Section: Discussionsupporting
confidence: 81%
“…When goals and ideas are understood by all team members, any potential confusion or conflict are discussed openly and productively (Tucker & Schwartz, 2013). In addition, acceptance of and openness to members' various cultures, backgrounds, experience, and knowledge are crucial throughout the collaborative process (Fewster-Thuente, 2015; Verdon, Wong, & McLeod, 2016).…”
Section: Conceptual Model (Based On Analysis)mentioning
confidence: 99%
“…They want professionals to presume they are willing and competent team members and to understand that life factors related to supporting children with diverse needs and/or health and employment commitments sometimes constrain their availability to engage in partnerships (McCormack, McAllister, McLeod, & Harrison, 2012). Parents' engagement may also be restricted by challenges understanding roles and processes (Dockrell et al, 2012), language and cultural barriers (Verdon, Wong, & McLeod, 2015) and anxiety about attending formal meetings (Ministry of Education, 2015).…”
Section: Partnershipmentioning
confidence: 99%